MECHANISM FOR ORGANIZING MUTUALLY BENEFICIAL ECONOMIC COOPERATION BETWEEN PARTICIPANTS IN THE DAIRY VALUE CHAIN (ON THE EXAMPLE OF SAMARKAND REGION) - Urazov Jamshidjon Sadullayevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The dairy production chain includes many interconnected entities - from product suppliers and milk producers to processors, distributors and retailers - whose coordinated interaction determines the overall efficiency and profitability of the sector. This article examines the mechanism for organizing mutually beneficial economic cooperation between these entities. It aims to develop an integrated framework that ensures co-creation of value, cost optimization and equitable distribution of benefits along the chain.